2013
DOI: 10.1002/mc.22043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variations in TERTCLPTM1L locus are associated with risk of lung cancer in chinese population

Abstract: Recent genome-wide association studies (GWAS) have reported multiple genetic variations at 5p15.33 (TERT-CLPTM1L) associated with risk of lung cancer. However, most of the associated variations identified by GWAS thus far are unlikely to be the actual causal variants, but may be mostly marker-single nucleotide polymorphisms tagging functional variations that influence gene expression. This study aimed to explore the function-validated and potentially functional variations in TERT-CLPTM1L locus conferring susce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(24 citation statements)
references
References 46 publications
2
21
1
Order By: Relevance
“…This rs2853669 SNP is also associated with a risk for other cancer types, such as breast cancer and especially lung cancer in the Asian population. [11-13, 26] As summarized in Table 2, the Asian population has the highest A>G allele fraction, and the glioblastoma patients in the present study have significantly lower frequency of the T/T allele and higher T/C and C/C frequency. Considering the lower incidence of glioblastoma in the Korean population (age-standardized rate of 0.59 per 100,000 person-years)[27] compared with that in the United States (age-standardized rate of 3.19 per 100,000 person-years),[28] it would be interesting to determine the frequency of the T349C SNP in glioblastoma patients of other ethnic groups.…”
Section: Discussionmentioning
confidence: 56%
“…This rs2853669 SNP is also associated with a risk for other cancer types, such as breast cancer and especially lung cancer in the Asian population. [11-13, 26] As summarized in Table 2, the Asian population has the highest A>G allele fraction, and the glioblastoma patients in the present study have significantly lower frequency of the T/T allele and higher T/C and C/C frequency. Considering the lower incidence of glioblastoma in the Korean population (age-standardized rate of 0.59 per 100,000 person-years)[27] compared with that in the United States (age-standardized rate of 3.19 per 100,000 person-years),[28] it would be interesting to determine the frequency of the T349C SNP in glioblastoma patients of other ethnic groups.…”
Section: Discussionmentioning
confidence: 56%
“…Yoo et al [16] showed that GG genotype of TERT rs2853669 A>G was significantly associated with increased lung cancer (LC) risk under a recessive model in the Korean population. Zhong et al [17] conducted a study for Chinese population and suggested that GG genotype of TERT rs2853669 A>G was also significantly associated with increased LC risk, especially with non-small lung cancer. Some other studies also reported the association of this gene with acute myeloid leukemia [18], prostate cancer [19] and breast cancer [20].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Yoo et al (2015) showed that GG genotype of hTERT rs2853669 A>G was significantly associated with increased LC risk under a recessive model in the Korean population. In Chinese population, it was found that GG genotype of hTERT rs2853669 A>G was also significantly related with an increased risk of LC, especially in nonsmall lung cancer and more prominent in adenocarcinoma (Zhong et al, 2013). Moreover, Mosrati et al (2015) reported that GG genotype of hTERT rs2853669 A>G polymorphism was a risk factor for the acute myeloid leukemia in Swedish population.…”
Section: Accepted Manuscriptmentioning
confidence: 97%